FlexiGIS: an open source GIS-based platform for the optimisation of flexibility options in urban energy systems. (October 2018) - Alhamwi, Alaa; Medjroubi, Wided; Vogt, Thomas; Agert, Carsten
Abstract: Climate change mitigation requires a fundamental transformation in the power supply system particularly in cities. Urban energy models integrated in Geographic Information Systems (GIS) have been playing a central role in shaping this transformation. In this regards, openness and transparency have been recently gaining a prominent importance and attracting increasing political interest. As renewables share has grown to high levels in cities, flexibilisation options including storage become vital to ensure a reliable, affordable and sustainable Urban Electricity System (UES). Energy modelling provides policymakers with qualitative and quantitative insights required for the planning and operation of future UES. Hence, the representation of UES requires an appropriate characterisation of different urban energy requirements that should be adequately incorporated in a spatial-temporal framework including both static and dynamic datasets. This paper introduces an open GIS-based platform for the optimisation of flexibility options costs and operation in urban areas. The platform reproduces the urban energy infrastructure (spatial dimension), simulates demand and supply (spatial and temporal dimension) and performs a linear programming optimisation to explore scenarios for the economic deployment of micro-generation and decentralised storage. The total UES costs and required storage capacities for different urban energy scenarios are investigated here. A key finding of this contribution is that investing in local electricity storage and on-site renewable power generation can significantly reduce the total system costs and increase urban self-sufficiency. The developed platform is showcased for the city of Oldenburg.